Yield management and the airlines industry: a new standard for predatory behavior - Ragazzo, Carlos Emmanuel Joppert (Revista do IBRAC, 2025)
Deregulation process. Structural changes in the airlines market in light of deregulation. Other effects of deregulation in the airlines market. Introduction of hub-and-spoke system and yield management techniques. Preliminary comment about the dilemma of predatory behavior of major airlines.